SIMULASI KREDIT MOBIL BEKAS PADA SHOWROOM BINTANG AUTO BERBASIS WEB: SIMULATON, CAR, PROMOTION - Pariyadi; Fitaloka, Wulan (LP2M STMIK Nurdin Hamzah Jambi, 2017)
Many people using vehicles such as cars, with different types, brands, and price of the car.Many people use the increasingly rapid development of technology to make the presentation of information can be done easily, quickly and efficiently. In the Bintang Showroom Auto current process of information services at Bintang Auto Showroom still using print media such as advertisements in newspapers and leaflets brochures, this is less efficient due to the additional cost. This is exactly what underlies doing research on Bintang Auto Showroom. In conducting the study, the authors used several research methodology, including. Media was built with support information using the programming language HTML, PHP, CSS, Java Script, Framewrok Bootstrap, Xampp as web servers, and My SQL as the database processing. Further media information that has been built is expected to further assist Bintang Auto Showroom car in conveying information to consumers, such as stock information automobile, car prices, car loans and simulation